Umedecimento do substrato e temperatura na germinação e vigor de sementes de melão - Vitorino, Hermeson dos Santos; Campos, Caio Ferraz de; Martins, Dagoberto [UNESP] (Univ Estadual Londrina, 2014)
The study was conducted to evaluate the efficacy of herbicides in desiccation Raphanus raphanistrum (wild radish) in different application times and their effects on weed seed germination. The experimental had a randomized block design with three replications. The herbicides used were: glyphosate (360; 720; and 1080 g ha(-1)), 2,4-D (335; 670; and 1005 g ha(-1)), glyphosate + 2,4-D (360 + 335; 720 + 670; and 1080 + 1005 g ha(-1)). Spraying was conducted at three different times: 1st season (full bloom) - at 62 days after emergence (DAE), 2nd season (beginning of pod formation) - at 92 DAE and 3rd season (end of pod formation) - at 108 DAE. At 14, 21, 28, 35, and 42 days after application (DAA), the desiccation was evaluated visually, and 42 DAA dry mass of shoots and seeds of the 2nd and 3rd times were collected for the test of germination. All chemical treatments tested were effective in controlling the plants of wild radish in the 1st and 2nd times, but in the 3rd time doses of 2,4-D applied singly were not effective and only the highest dose of glyphosate applied singly or in mixture provided a total plant control. In terms of percentage, the reduction in dry matter of plants was higher with the application of larger doses of chemical treatments. The herbicides affected the germination of seeds of wild radish, and the herbicide 2,4-D provided greater reduction in germination in the 2nd and 3rd seasons.
Effect of herbicides on wild radish and seed germination
Keywords: Chemical control; no-tillage; glyphosate; 2,4-D